Investigations on energy input-output in below sea level rice production systems in Kuttanad region of Kerala - NIDHIN J.K (Tavanur 2017 DEPARTMENT OF FARM POWER, MACHINERY AND ENERGY)
Investigations on energy input-output in below sea level rice production systems in Kuttanad region of Kerala
Investigations on energy input-output in below sea level rice production systems in Kuttanad region of Kerala